RENCANA PENGEMBANGAN TEKNIK OPERASIONAL SISTEM PENGELOLAAN SAMPAH KOTA JUWANA - Wardhana, Irawan Wisnu (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Juwana city is one of a developed potential region that include in a WANARAKUTI (Juwana-Jepara-Kudus Pati) economic unity region. It has 43,282 populations in 2005 with the growth rate  of  populations  was about  1.308%  per  year. The  developing  of  populations  was  followed with the increasing of consumption quantities and other activities which increased production of solid wastes. In 2005, the amount of solid wastes was 133.896 m3/day and the development of bulk sizes of these wastes was 0.4% per year. Ranking of waste management service was 39% and service distribution was 50,47%. One of important aspects that caused low quality of waste management  services  was  the  aspects  operational technology  usage.  It  included  of  waste handling, storage, collection, transfer and transport. The evaluation and development program of waste operational technology was to increase the distribution area and service management of solid wastes up to 90%.